Disparities in the analysis of morphological disparity. (29th July 2020) - Guillerme, Thomas; Cooper, Natalie; Brusatte, Stephen L.; Davis, Katie E.; Jackson, Andrew L.; Gerber, Sylvain; Goswami, Anjali; Healy, Kevin; Hopkins, Melanie J.; Jones, Marc E. H.; Lloyd, Graeme T.; O'Reilly, Joseph E.; et al.
Abstract : Analyses of morphological disparity have been used to characterize and investigate the evolution of variation in the anatomy, function and ecology of organisms since the 1980s. While a diversity of methods have been employed, it is unclear whether they provide equivalent insights. Here, we review the most commonly used approaches for characterizing and analysing morphological disparity, all of which have associated limitations that, if ignored, can lead to misinterpretation. We propose best practice guidelines for disparity analyses, while noting that there can be no 'one-size-fits-all' approach. The available tools should always be used in the context of a specific biological question that will determine data and method selection at every stage of the analysis.